Do bilingual and monolingual preschoolers acquire false belief understanding similarly? The role of executive functioning and language. Issue 4 (August 2018) - Diaz, Vanessa; Farrar, M. Jeffrey
Bilingual children often show advanced executive functioning (EF) and false belief (FB) understanding compared to monolinguals. The latter has been attributed to their enhanced inhibitory control EF, although this has only been examined in a single study which did not confirm this hypothesis. The current study examined the relation of EF and language proficiency on FB reasoning in bilingual and monolingual preschoolers to answer two questions: (1) Are there differences in bilinguals' and monolinguals' FB, language proficiency, and EF? If so, (2) is there a differential role for language proficiency and EF in predicting FB reasoning in these two groups? Thirty-two Spanish–English bilinguals and 33 English monolinguals (three to five years old) were compared. While monolinguals outperformed bilinguals on language proficiency, after controlling for this, bilinguals outperformed monolinguals on FB reasoning, and marginally on EF. General language ability was related to FB performance in both groups, while short-term memory and inhibitory control predicted FB only for monolinguals.